In vivo three-dimensional lamina cribrosa strains in healthy, ocular hypertensive, and glaucoma eyes following acute intraocular pressure elevation - Beotra, M.R. (Association for Research in Vision and Ophthalmology Inc., 2021)
10.1167/iovs.17-21982